Суперелементна модель каркаса кузова туристичного автобуса - Горбай, О. З. (My University, 2016)
Розраховуючи каркас кузова автобуса на рівноміцність, використати суперелементне 3D-моделювання, що дає змогу створити модель повної конструкції туристичного кузова автобуса з можливістю розбиття його на сукупність підконструкцій на рівнях. Рівновага складових цього типу кузова досягається побудовою ієрархії підструктур. Під час дискредитації моделі використано поділ каркаса кузова вертикально поперечними площинами на окремі просторові об’єми призматичного типу. Розрахунок каркаса кузова на міцність проведено за умови забезпечення європейських вимог пасивної безпеки. Досліджувана модель характеризується значеннями переміщень у структурі каркаса мотовідсіка у межах 6–7,5 мм. Відносне переміщення точок кріплення силового приводу на двох опорах під двигуном та двох – під трансмісією не перевищує 5 мм, що знаходиться у допустимих межах для нормальної спільної роботи двигуна й трансмісії. Сalculation of the index of the strength of the body shell regarding the conditions of passive safety made on final superelement of FE 3D modeling. It is made possible to create a complete model a bus frame structure with the partitioning the set of substructures in the levels. This method of partitioning a bus body structure to superelements is a method of a series-parallel procedures designed to handle equilibrium of the object. The balance of the components of the body was achieved by hierarchy of sub-structures. The basic finite element of substructure is located on the first level, whereas the full model object is a substructure of the highest level. Superelement in FE model makes it possible to consider them at every level as substructures in contact to only at the boundary nodes. Separation of the body of the frame is performed by vertical transverse plane into separate spatial volum’s of prismatic type. The calculation of body frame strength provided according European standards of passive safety. The researched model got the displacement of structure of motor compartment frame within 6–7,5 mm.. Displacement of fixing supports of engine and transmission is less than 5 mm, which is within acceptable limits for common engine and transmission work.
Keywords: міцність; кузови автобусів; пасивна безпека; Правила ЄЕК ООН; МСЕ; strength; bus frame; passive safety; requirements UN/ECE; FE